Televiewing, study habits, and home activities of U.P. Elementary School children - Nacino, Remedios M. 1944- (s.n.], 1968)
This study investigated the influence of television on the study habits and home activities of elementary school children in the University of the Philippines. Results show that: television children usually come from well-to-do families, and belong to a high occupational and income group in the locality; among children, television viewing varies in accordance with their age and sex; television has marked effects on the home and leisure time activities of the children; and lastly, parents tend to supervise and control their children's veiwing time.